Nickel-catalyzed C-H bond functionalization of azoles and indoles - Jagtap, Rahul A.; Punji, Benudhar (Chemical Record, 2021)
Direct C-H functionalization of privileged and biologically relevant azoles and indoles represents an important chemical transformation in molecular science. Despite significant progress in the palladium-catalyzed regioselective C-H functionalization of azoles and indoles, the use of abundant and less expensive nickel catalyst is underdeveloped. In the recent past, the nickel-catalyzed regioselective C-H alkylation, arylation, alkenylation and alkynylation of azoles and indoles have been substantially explored, which can be applied to the complex organic molecule synthesis. In this Account, we summarize the developments in nickel-catalyzed regioselective functionalization of azoles and indoles with a considerable focus on the reaction mechanism.
Keywords: azoles; C-C Bond formation; C-H functionalization; indoles; Nickel